Changes in oat grain yield and quality with increased adaptability of cultivars - P. N. Nikolaev; O. A. Yusova; I. V. Safonova; N. I. Aniskov (Труды по прикладной ботанике, генетике и селекции)
Background. Among spring cereals, oat is one of the main grain crops in Siberia. The aim of this study was to determine how the parameters of adaptability in oat cultivars are correlated with yield and basic indicators of grain quality.Material and methods. The studies were carried out from 2011 to 2019 in the southern forest steppe of Western Siberia. The content of protein, crude fat and starch in grain, and its hull content were measured according to B. V. Pleshkov and N. S. Berkutova. Mathematical processing was performed following the guidelines by B. A. Dospekhov, S. A. Eberhart and W. A. Russell.Results. There was a significant variation in grain yield and grain quality (CV > 20%) in oat cultivars due to a high contribution from the conditions of the year (26.7...80.9%) as well as a strong direct (r = 0,607...0.825) or strong reverse (r = –0.660...–0.994) conjugation with climatic factors. As the protein content in grain increased, starch, oil (r = 0.960...0.962) and hull content (r = 0.442) increased as well. Naked oat cultivars manifested higher grain quality (4.6% protein, 17.6% starch, and 2.2% crude fat) and reduced yield (–1.45 t/ha) compared with hulled oat cultivars.Conclusion. Increased plasticity (bi) and stability (σ2d) of oat cultivars contributed to higher yields (rbi = 0.943;rσ2d = 0.344) but reduced grain quality indicators (rbi = –0.697…–0.812;rσ2d = –0.270…–0.300). Hull content in plastic cultivars decreased (rbi = –0.201).